Dynamics of sectoral business cycle comovement - Anna Pauliina Sandqvist (ETH Zurich, KOF Swiss Economic Institute, 2015)
In this paper a multivariate dynamic conditional correlation (DCC) general autoregressive conditional heteroskedasticity (GARCH) framework is employed to study dynamics of sectoral comovement across manufacturing sectors both in Germany and in the United States. Asymmetric effects both in conditional volatilities as well as in conditional correlations are being assessed, which have hardly been considered in intersectoral comovement studies by now. We find that comovement across sectors is not stable, but fluctuates substantially. Particularly, sectoral comovement in German and US manufacturing seem to have increased considerably during some recesssion periods, especially in the recession of 2008-2009, but not during every recession. Moreover, we examine the role of stock market volatility respectively uncertainty for the dynamic correlations and find it to have a signifificant effect in both countries.
Keywords: E32; C32; 330; business cycles; sectoral comovement; time-varying correlations; DCC-GARCH